Pengaruh Pendampingan Dengan Melibatkan Ibu-Ibu PKK terhadap Pengendalian Berat Badan Ibu Hamil - Nova S.J Sianturi; Yessy Arisman; Krisdamayanti Harefa (Jurnal Bidan Mandiri, 2024)
Assistance for pregnant women is one form of community service aimed at enhancing community involvement in efforts to improve the health of mothers and children. One effort to reduce maternal mortality rates is maximizing support for pregnant women. Antenatal Care (ANC) services monitor the weight of pregnant women, as physiological changes are associated with a 25% increase in body weight during pregnancy. Weight gain during pregnancy is expected to occur in the second and third trimesters at a rate of 0.5 kg per week. The research aims to determine the influence of assistance involving PKK (Family Welfare Movement) mothers on the control of pregnant women's weight. This study is a Quasi-Experiment using a non-equivalent control group design. The sample consists of 28 pregnant women divided into two groups (intervention and control), and data were collected using observation sheets. Data analysis employed the Wilcoxon test. The results showed a significant difference between the Control and Intervention groups, indicating the influence of assistance on the Intervention group (p-value = 0.025 < 0.05). Therefore, the involvement of PKK mothers has an impact on controlling the weight of pregnant women. It is hoped that healthcare professionals and PKK mothers can support pregnant women in managing their weight.